2009
DOI: 10.1155/2009/474360
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal Activity of SomeSolanumSpecies Extracts against the SnailBiomphalaria alexandrina

Abstract: Background. Snails' species are associated with transmission parasitic disease as intermediate host. Biological control stands to be a better alternative to the chemical controls aimed against snails. The search of herbal preparations that do not produce any adverse effects in the non-target organisms and are easily biodegradable remains a top research issue for scientists associated with alternative molluscicides control. Method. Solvent extracts of fresh mature leaves of S. nigrum, S. villosum, and S. sinai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Despite all recent research and development current synthetic molluscicides also raise serious environmental concerns and threats to both human health and income (particularly in areas where fishing is a major source of food and income) due to their lack of specificity (Andrews et al 1982;He et al 2017). Thus, identifying or developing more selective molluscicidal herbal preparations that do not have adverse effects (or at least acceptably weak effects) in non-target aquatic organisms and are biodegradable remains a high priority (El-Sherbini et al 2009).…”
Section: Synthetic Molluscicidesmentioning
confidence: 99%
“…Despite all recent research and development current synthetic molluscicides also raise serious environmental concerns and threats to both human health and income (particularly in areas where fishing is a major source of food and income) due to their lack of specificity (Andrews et al 1982;He et al 2017). Thus, identifying or developing more selective molluscicidal herbal preparations that do not have adverse effects (or at least acceptably weak effects) in non-target aquatic organisms and are biodegradable remains a high priority (El-Sherbini et al 2009).…”
Section: Synthetic Molluscicidesmentioning
confidence: 99%
“…Sokkal szorosabb az RDA kapcsolata az 1998-ban publikált Functional Requirements for Bibliographic Records (FRBR) elnevezésű ajánlásokkal, 5 ahogy El-Sherbini fogalmaz: "az egész RDA az FRBR-gondolaton alapul". 6 Az FRBR filozófiája az entitások gondolatára és a köztük lévő kapcsolatrendszerre épül. Korábban a katalogizálók csak a megjelenési formákat írták le, figyelmen kívül hagyva a mű és a kifejezési forma szintjét, valamint a köztük lévő összefüggéseket.…”
Section: Az Internet Terébenunclassified
“…"A katalogizáló tevékenységnek nem az a célja, hogy a könyvet levegyük a polcról, azt meg is kell találnia valakinek.". 7 Ha a katalogizálás legnagyobb eredménye a használók és a könyvtári források közti kapcsolat megteremtése, akkor ezek a változtatások a kapcsolatot könnyebbé, szorosabbá és erősebbé teszik.…”
Section: Az Internet Terébenunclassified
“…has been reported by many re searchers) Farag 2017; Ibrahim et al 2022). El-Sherbini et al (2009) studied the molluscicidal activity of Solanum nigrum against Biomphalaria alexandrina (Ehrenberg). They found that extracts from mature leaves of Solanum species exhibited molluscicidal activities.…”
Section: Introductionmentioning
confidence: 99%